(untitled) (Heritage, 2021)
The subject of this paper is a way of conceptualizing God in the Serbian language. The aim of the paper is to show and indicate the ways in which the meaning of the noun god is understood in the Serbian language, and which metaphors arise when it is described. It is shown which metaphorical expressions are and by which source domains the concretization occurs. The theoretical basis of the conducted research is the theory of conceptual metaphors, which is based on the cognitive-semantic approach. First, a theoretical review of conceptual metaphors is given, followed by an analysis of a corpus based on examples from literary works, daily newspapers, and dialect texts from the Kragujevac Lepenica area.